1997
DOI: 10.1128/iai.65.11.4598-4605.1997
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii sporozoites form a transient parasitophorous vacuole that is impermeable and contains only a subset of dense-granule proteins

Abstract: Toxoplasma gondii sporozoites form two parasitophorous vacuoles during development within host cells, the first (PV1) during host cell invasion and the second (PV2) 18 to 24 h postinoculation. PV1 is structurally distinctive due to its large size, yet it lacks a tubulovesicular network (C. A. Speer, M. Tilley, M. Temple, J. A. Blixt, J. P. Dubey, and M. W. White, Mol. Biochem. Parasitol. 75:75-86, 1995). Confirming the finding that sporozoites have a different electron-dense-granule composition, we have now fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…1C1*). As we have shown previously, replicating parasites in sporozoite‐infected cells reside in a vacuole that is structurally distinct from the primary vacuole formed during sporozoite invasion (Tilley et al ., 1997). It is intriguing that sporozoite‐specific proteins are absent from the parasitophorous vacuole space and membrane in Fig.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…1C1*). As we have shown previously, replicating parasites in sporozoite‐infected cells reside in a vacuole that is structurally distinct from the primary vacuole formed during sporozoite invasion (Tilley et al ., 1997). It is intriguing that sporozoite‐specific proteins are absent from the parasitophorous vacuole space and membrane in Fig.…”
Section: Resultsmentioning
confidence: 58%
“…Note staining of sporozoite surface, cytoplasm, and parasitophorous vacuole 2 h post invasion which is lost at later times. CPA cells are shown here as the relatively larger vacuole size formed (Tilley et al ., 1997) in these cells readily demonstrate secreted antigen(s), similar results are observed using HFF monolayers (data not shown). Molecular mass markers (kDa) are indicated to the left of (A,B).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…While T. gondii oocysts and sporozoites have been studied extensively for their ability to cause disease in intermediate hosts (13, 19, 20), very little is known about the biology of H. hammondi oocysts and sporozoites. We compared sporozoite yield and infectivity between T. gondii and H. hammondi using oocyst preparations derived from multiple cat infections and consistently found that the yield of sporozoites from HhCatEth1 was lower than that from TgVEG oocysts.…”
Section: Resultsmentioning
confidence: 99%